TAP Block in Children: Does Inflammation Affect on Pain Score? - B., Odgerel; O., Sergelen; L., Ganbold (International Journal of Innovative Research in Medical Science, 2018)
Objective: The aim of this study was to evaluate of analgesic effect of ultrasound guided transversus abdomines plane (TAP) block in children undergoing open laparotomy surgery and compare to children were used general anesthesia (GA) alone. Methods: 60 children aged 3-18 years with ASA I-III classification were randomly enrolled in this study. We divided these children in to two groups: control group (GA alone, n=31) and study group (GA+TAP block, n=29) and also divided each group in two subgroups which were with inflammation and without inflammation. All children were received GA with same techniques. Study group (TAP block group) were assigned to receive ultrasound guided block in both side of abdomen using 0.3 ml/kg of Bupivacaine 0.25%, but not more than 12 ml in each side. Hemodynamic variables such as heart rate, blood pressure were measured at baseline (T0), after induction (T1), after skin incision (T2), and end of surgery (T3), and in the recovery room or ICU, at the 2nd, 4th, 6th hours postoperatively and examined pain intensity and analgesic requirement and frequency, also correllation between inflamatory process and pain intensity were studied. Statistic analysis was made in Excel using ANOVA, descriptive analysis, correlation and regression analysis. A p-value<0.05 was considered significant. Results: There was no differencies between the two studied groups regarding demographic and clinical characteristics. Intraoperative heart rate elevation was higher in GA group with an inflammation (13.3%) and the systolic blood pressure changes was higher (4.2%) after skin incision than study group and GA group without inflammation. Level of WBC had very weak positive and statistically significant correlation with intraoperative opioid usage (GA+Inf: r=0.029, p=0.023; ТAP+Inf: r=0.18, p=0.016; GA-Inf: r=0.018, p=0.014) but there was not observed correlation in TAP-Inf group. Postopeative pain score was higher in control group and an analgesic requirement and frequency was much more. Conclusion: Transversus abdomines plane block under ultrasound guidance was easy, safe, reliable and effective analgesic in children undergoing open laparotomy surgery and TAP block is a good component of postoperative multimodal analgesia. The inflammatory process increases pain intensity and intra and postoperative analgesic requirements.